S / Fe co-doped magnetic porous carbon material and preparation method and application thereof

By using S/FE co -doped magnetic porous carbon materials as a catalyst, the problem of low catalytic activity, poor durability and difficulty recycling in existing technologies have been solved, and the effect of high -efficiency removal of chloroly phenol pollutants has high catalytic activity, and has high catalytic activity, and it has high catalytic activity. Stability and good recycling.

CN119368211AActive Publication Date: 2025-01-28CENT SOUTH UNIV

Patent Information

Application Number
CN202411583304.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-07
Publication Date
2025-01-28
Estimated Expiration
2044-11-07

AI Technical Summary

Technical Problem

Existing periodate-mediated advanced oxidation techniques have problems of low catalytic activity, poor durability and difficulty in recycling when removing chlorophenol pollutants.

Method used

The S/FE co -doped magnetic porous carbon material is used as a catalyst. This material is synthesized by the water thermal method, including the hybrid structure of ZNS, FE3C and porous carbon, which enhances the surface area and catalytic activity, and through segmented thermal solution and acid Miscellaneous treatment improves the stability and recycling of materials.

Benefits of technology

Achieve efficient and thoroughly remove the chlorophenol organic pollutants in the water body, which has high catalytic activity, strong stability, and is easy to separate and reuse. Essence

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119368211A_ABST
    Figure CN119368211A_ABST
Patent Text Reader

Abstract

The invention discloses an S / Fe co-doped magnetic porous carbon material as well as a preparation method and application thereof. The preparation method of the S / Fe co-doped magnetic porous carbon material comprises the following steps: mixing a 2-methylimidazole solution, a zinc salt solution and an organic iron solution for hydrothermal reaction to obtain an iron-containing zeolite imidazate framework precursor; dispersing the iron-containing zeolite imidazate framework precursor and elemental sulfur in a solvent, and heating to obtain an S / Fe co-doped magnetic porous carbon material precursor; and performing high-temperature pyrolysis on the S / Fe co-doped magnetic porous carbon material precursor in a protective atmosphere to obtain the S / Fe co-doped magnetic porous carbon material. The porous carbon material has the advantages of large specific surface area, abundant pore structure, multiple catalytic sites and high stability, can efficiently catalyze periodate to degrade chlorophenol organic pollutants in wastewater, and has the advantages of thorough removal effect, no secondary pollution, good application prospect, simple preparation method, low cost and suitability for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a carbon material, in particular to an S / Fe co-doped magnetic porous carbon material, and also to a preparation method and application thereof, belonging to the technical field of carbon material preparation and environmental governance. Background Art

[0002] Chlorophenols (CPs) are a class of chlorinated aromatic compounds containing benzene rings, hydroxyl groups and different numbers of chlorine atoms. Due to their unique reaction characteristics and strong antibacterial properties, they are widely used in both industrial and agricultural fields. This also causes CPs to be inevitably released into the ecological environment. For example, it is estimated that the CPs waste generated by various industries such as lumber mills, paper mills, and pesticide production plants in the United States alone exceeds 1,900 tons per year. The π electrons on the benzene ring and the p orbitals on the chlorine atoms can form a stable conjugated system, resulting in strong chemical stability of CPs, and they are difficult to be biodegraded. They can exist in the natural environment for a long time, so they are also a class of environmental pollutants with a large number at present. Because CPs are highly toxic, persistent, and have "three-cause effects" (carcinogenic, teratogenic, and mutagenic), and the more chlorine atoms are connected to the benzene ring, the higher the toxicity, which poses a serious threat to ecological security and human health. They have been listed in the list of priority controlled pollutants by countries and regions including my country and the European Union. Therefore, the efficient removal of CPs pollution in water bodies has become an important environmental issue facing humans today.

[0003] Advanced oxidation processes (AOPs) are the most commonly used method for removing chlorophenol pollutants due to their advantages of being fast, efficient, simple to operate, mild conditions, and environmentally friendly. Among them, periodate-mediated AOPs have attracted the attention of many scholars due to their high efficiency, stability, and ease of storage and transportation. - , E0 = 1.60 V) has limited kinetic activity for the degradation of organic pollutants, but a variety of active substances with strong oxidizing properties, such as reactive oxygen species (ROS) and reactive iodine (RIS), produced by activation can efficiently degrade organic pollutants and have broad application prospects in the treatment of chlorophenol wastewater. A large number of studies have confirmed that transition metal-based catalysts can efficiently activate periodate, but the narrow pH range of application and the high risk of leaching toxic metal ions under oxidative and acidic reaction conditions severely limit the practical application of this technology. In recent years, metal-free carbon-based catalysts have shown potential application value in periodate-mediated AOPs due to their advantages such as high stability, high conductivity and acid and alkali resistance, and have attracted great attention. However, metal-free carbon-based catalysts have inherent problems such as low activity, low durability and difficulty in recycling.

[0004] Therefore, providing a carbon-based catalyst with good catalytic performance, high stability, easy recovery and precise control is of great significance for the efficient and thorough removal of chlorophenol pollutants in wastewater. Summary of the invention

[0005] In view of the shortcomings of the prior art, the first object of the present invention is to provide a S / Fe co-doped magnetic porous carbon material. The material has excellent catalytic performance, is stable and strong, is easy to recover and can be recycled.

[0006] The second object of the present invention is to provide a method for preparing S / Fe co-doped magnetic porous carbon material. The method is simple, low-cost and suitable for industrial production.

[0007] The third object of the present invention is to provide an application of a S / Fe co-doped magnetic porous carbon material, which has high catalytic activity and can greatly improve the treatment efficiency when used to catalyze periodate oxidation and degradation of chlorophenol organic pollutants in a solution.

[0008] In order to achieve the above technical objectives, the present invention provides a method for preparing an S / Fe co-doped magnetic porous carbon material, which comprises mixing a 2-methylimidazole solution with a zinc salt solution and an organic iron solution for hydrothermal reaction to obtain an iron-containing zeolite imidazolate skeleton precursor; dispersing the iron-containing zeolite imidazolate skeleton precursor and elemental sulfur in a solvent and heating them to obtain an S / Fe co-doped magnetic porous carbon material precursor; and subjecting the S / Fe co-doped magnetic porous carbon material precursor to high-temperature pyrolysis under a protective atmosphere to obtain the obtained material.

[0009] The present invention not only retains the regular dodecahedron morphology of the MOF precursor by doping the carbon material with S and Fe, but also effectively changes its electronic configuration by adding iron to the carbon skeleton, reduces the chemical inertness of the carbon-based material, and makes the surface of the material rough and concave, forming a hybrid structure composed of ZnS, Fe3C and porous carbon, which increases the specific surface area, optimizes the layered porous structure, and enhances the surface active sites. It also has good magnetic properties and is easy to separate and reuse. Compared with the loaded metal sulfide, the present invention heat-treats the iron-containing precursor with elemental sulfur. The suitable nanocavity and small pore size of ZIF-8 can encapsulate the iron source, which can overcome the defects of metal leaching of traditional carbon-loaded metal sulfides. After pyrolysis, Fe-ZIF-8 can generate Fe3C containing various valence states of Fe, and ZIF-8 contains abundant Zn elements that can form ZnS with S atoms in a directional manner. S 2- It can accelerate the circulation of Fe in the catalytic process and further improve the catalytic performance.

[0010] As a preferred embodiment, the molar ratio of the 2-methylimidazole to the zinc element in the zinc salt and the iron element in the organic iron solution is (0.5-1.5):(0.1-0.3):(0.01-0.03).

[0011] As a preferred solution, the concentration of the 2-methylimidazole solution is 1-2 mol / L.

[0012] As a preferred solution, the concentration of the zinc salt solution is 0.1-0.2 mol / L.

[0013] As a preferred solution, the concentration of the organic iron solution is 0.01-0.02 mol / L.

[0014] As a preferred embodiment, the zinc salt is zinc nitrate.

[0015] As a preferred solution, the organic iron is ferric acetylacetonate. The ferric acetylacetonate used in the present invention, whose organic ligand-derived n-doped carbon matrix can effectively disperse and stabilize Fe species, prevent their aggregation and leaching, and can also prevent ZIF-8 from collapsing to a certain extent during the carbonization process.

[0016] As a preferred solution, the conditions of the hydrothermal reaction are: temperature of 110-140° C. and time of 2-4 h.

[0017] As a preferred solution, the mass ratio of the iron-containing zeolite imidazolate framework precursor to elemental sulfur is not less than 6:1.

[0018] As a preferred solution, the mass ratio of the iron-containing zeolite imidazolate framework precursor to elemental sulfur is 6 to 12: 1. Controlling the amount of elemental sulfur within a suitable range is beneficial to improving the catalytic performance of the material. Too high a sulfur dosage will result in too high a sulfur doping amount, causing the material structure to collapse and resulting in a decrease in catalytic performance; too low a sulfur dosage will result in too low a doping amount and a relatively reduced catalytic activity of the material.

[0019] As a preferred solution, the solvent is a mixed solvent of carbon tetrachloride and ethanol.

[0020] As a preferred solution, the heating temperature is 50-80°C.

[0021] As a preferred solution, the protective atmosphere is an inert gas atmosphere.

[0022] As a preferred solution, the inert gas is argon.

[0023] As a preferred solution, the high-temperature pyrolysis process is: first pyrolyze at a temperature of 400-500°C for 2-4 hours, and then heat to 900-1000°C for 4-6 hours.

[0024] The present invention uses segmented pyrolysis to buffer the S / Fe co-doped magnetic porous carbon material precursor, reduce the damage to its structure caused by high temperature, and effectively avoid the phenomenon of serious collapse of the material structure caused by directly using 900~1000℃ pyrolysis of the precursor. The present invention first performs a stage pyrolysis at a relatively low temperature to remove the unstable S element wrapped on the surface of the S / Fe co-doped magnetic porous carbon material precursor, and serves as a buffer for the second stage of heating; then a high-temperature second stage pyrolysis is performed to remove excess Zn element, exposing more pores and specific surface area. The present invention adopts a two-stage temperature rise pyrolysis method, which can remove excess impurities, expose more pores, and maintain the structural stability of the material, which helps to improve the adsorption of periodate and chlorophenol organic matter, thereby improving its performance of activating periodate to degrade chlorophenol organic matter.

[0025] As a preferred solution, the high-temperature pyrolysis is followed by an acid leaching and impurity removal treatment.

[0026] As a preferred solution, the conditions for the acid leaching and impurity removal treatment are: sulfuric acid is used as the acid leaching solution, the sulfuric acid concentration is 0.2-0.8 mol / L, and the acid leaching time is 6-10 hours.

[0027] The present invention also provides a S / Fe co-doped magnetic porous carbon material, which is prepared by the above method. The material has a large specific surface area, a reasonable layered porous structure, abundant active sites on the surface, high catalytic activity and stable performance.

[0028] The present invention also provides an application of a S / Fe co-doped magnetic porous carbon material, which is used for catalyzing periodate oxidation and degradation of chlorophenol organic pollutants in a solution.

[0029] When the S / Fe co-doped magnetic porous carbon material in the present invention activates periodate, its active sites are mainly C=O, graphite N functional groups and Fe-based nanoparticles, while the reducing S 2- Active substances are continuously generated by promoting the redox cycle of Fe species, and the system also has an electron transfer process, that is, free radicals and non-free radical pathways act together on the degradation of chlorophenol organic matter, thereby achieving efficient and thorough removal of chlorophenol organic pollutants. The present invention achieves efficient degradation of chlorophenol organic pollutants, has the advantages of high treatment efficiency, good effect, simple operation, small amount of added chemicals, easy separation, environmental protection, etc., and can avoid the shortcomings of high Fe and Zn ion leaching and generation of toxic iodine by-products during periodate activation, and IO3· is selective for the removal of pollutants. The relevant reaction principle is as follows:

[0030] As a preferred solution, the concentration of the S / Fe co-doped magnetic porous carbon material in the solution containing chlorophenol organic pollutants is 0.025-0.1 g / L.

[0031] As a preferred solution, the concentration of the periodate in the solution containing chlorophenol organic pollutants is 5-15 mM.

[0032] As a preferred solution, the concentration of the chlorophenol organic pollutants in the solution does not exceed 40 mg / L.

[0033] As a preferred embodiment, the chlorophenol organic pollutant is p-chlorophenol.

[0034] As a preferred solution, the initial pH value of the solution containing chlorophenol organic pollutants is 3 to 9. Controlling the initial pH value of the solution containing chlorophenol organic pollutants within a suitable range can ensure that the catalytic activity of the S / Fe co-doped magnetic porous carbon material is at a high level and improve the catalytic efficiency.

[0035] Compared with the prior art, the present invention has the following beneficial effects: (1) Compared with traditional carbon materials, the S / Fe co-doped magnetic porous carbon material of the present invention retains the regular dodecahedron morphology of the MOF precursor, but the surface is rough and concave. It is a hybrid structure composed of ZnS, Fe3C and porous carbon. The specific surface area, hierarchical porous structure and surface active sites are significantly enhanced. It has excellent catalytic activity, strong stability, good magnetic properties, and is easy to separate, recycle and reuse. It also has the advantages of low preparation cost and environmental protection. (2) The S / Fe co-doped magnetic porous carbon material of the present invention can be used to catalyze the periodate oxidation degradation of chlorophenol organic pollutants in the solution, and has a good catalytic effect, and can achieve efficient and thorough removal of chlorophenol organic pollutants in the solution under room temperature conditions; (3) The preparation method is simple, low-cost and suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 These are scanning electron microscope images of the S / Fe co-doped magnetic porous carbon material (a), magnetic porous carbon material (b), S-doped magnetic porous carbon material (c), and Fe-doped magnetic porous carbon material (d) in Example 1 of the present invention; and transmission electron microscope images (e, f), high-resolution transmission electron microscope images (g, h), annular selected area electron diffraction images (i), HADDF-STEM images (j) and corresponding EDS element mapping images of the S / Fe co-doped magnetic porous carbon material.

[0037] Figure 21 and 2. These are X-ray diffraction analysis diagrams of the magnetic porous carbon material, S-doped magnetic porous carbon material, Fe-doped magnetic porous carbon material and S / Fe co-doped magnetic porous carbon material in Example 1 of the present invention.

[0038] Figure 3 This is a diagram showing the removal effect of p-chlorophenol in wastewater under the same reaction conditions by the zeolite imidazolate framework material, iron-containing zeolite imidazolate framework, S / Fe co-doped zeolite imidazolate framework, magnetic porous carbon material, Fe-doped magnetic porous carbon material, S-doped magnetic porous carbon material, and S / Fe co-doped magnetic porous carbon material in Example 2 of the present invention.

[0039] Figure 4 This is a diagram showing the removal effect of p-chlorophenol in wastewater by S / Fe co-doped magnetic porous carbon materials with different added amounts in Example 3 of the present invention.

[0040] Figure 5 This is a diagram showing the removal effect of para-chlorophenol in wastewater by S / Fe co-doped magnetic porous carbon material under different initial pH conditions in Example 4 of the present invention.

[0041] Figure 6 This is a diagram showing the effect of different S-doping amounts of magnetic porous carbon materials on the removal of para-chlorophenol in water in Example 5 of the present invention.

[0042] Figure 7 This is the cyclic stability diagram of S / Fe co-doped magnetic porous carbon materials. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with the accompanying drawings and specific preferred embodiments, but the protection scope of the present invention is not limited thereby.

[0044] The raw materials and instruments used in the following examples are all commercially available. In the examples of the present invention, unless otherwise specified, the data obtained are the average values ​​of more than three repeated experiments. Example 1

[0045] The S / Fe co-doped magnetic porous carbon material of the present invention is mainly prepared by reacting an iron-containing zeolite imidazolate skeleton precursor synthesized by a hydrothermal method with sulfur powder and then heat-treating the precursor, and specifically comprises the following steps: S1. Rapidly add 2L of a mixed solution of 0.13mol / L zinc nitrate and 0.013mol / L ferric acetylacetonate into 1L of a 1mol / L 2-methylimidazole solution, stir for 1 hour, transfer to a stainless steel autoclave lined with polytetrafluoroethylene, heat at 120°C for 4 hours, wash and dry to obtain an iron-containing zeolite imidazole framework precursor, recorded as Fe-ZIF-8.

[0046] S2. The iron-containing zeolite imidazolate framework precursor and sulfur powder (Fe-ZIF-8: sulfur powder mass ratio = 10:1) prepared in step S1 are mixed and dispersed in 1L of a mixed solvent of carbon tetrachloride and ethanol (V / V = 4:1), stirred vigorously at 60°C, and evaporated to dryness to obtain a S / Fe co-doped zeolite imidazolate framework precursor, recorded as S / Fe-ZIF-8.

[0047] S3, the iron / sulfur doped zeolite imidazolate framework precursor prepared in step S2 was heated at 5°C min -1 The temperature was raised to 450 °C and 950 °C for 2 hours and 4 hours respectively. After cooling, it was suspended in a 0.5 mol / L H2SO4 solution at 80 °C and acid-leached for 8 hours. The material was washed and dried to obtain S / Fe co-doped magnetic porous carbon material, which was recorded as S / Fe-ZIF-950. Comparative Example 1

[0048] The carbon material was prepared by the method of Example 1, except that: ferric acetylacetonate was not added in step S1 to obtain the zeolite imidazolate framework precursor ZIF-8, and the sulfur doping treatment of step S2 was not performed. ZIF-8 was directly pyrolyzed by the method of step S3 to obtain a porous carbon material, which was recorded as ZIF-950. Comparative Example 2

[0049] The carbon material was prepared by the method of Example 1, except that: no ferric acetylacetonate was added in step S1 to obtain the zeolite imidazolate framework precursor ZIF-8, and then the iron-containing zeolite imidazolate framework precursor in step S2 was replaced by ZIF-8 to obtain S / ZIF-8, and the iron / sulfur-doped zeolite imidazolate framework precursor in step S3 was replaced by S / ZIF-8 to obtain an S-doped porous carbon material, recorded as S-ZIF-950. Comparative Example 3

[0050] The carbon material was prepared by the method of Example 1, except that the sulfur doping treatment in step S2 was not performed, and the iron / sulfur-doped zeolite imidazolate framework precursor in step S3 was directly replaced by Fe-ZIF-8 to obtain Fe-doped magnetic porous carbon material, which was recorded as Fe-ZIF-950.

[0051] The S / Fe co-doped magnetic porous carbon material S / Fe-ZIF-950 prepared in Example 1, the porous carbon material ZIF-950 prepared in Comparative Example 1, the S-doped porous carbon material S-ZIF-950 prepared in Comparative Example 2, and the Fe-doped magnetic porous carbon material Fe-ZIF-950 prepared in Comparative Example 3 were observed by scanning electron microscopy. The results are as follows: Figure 1 As shown in (a~d), from Figure 1As can be seen in (a), after high-temperature carbonization, the S / Fe-ZIF-950 prepared in Example 1 of the present invention can well retain the original regular dodecahedron morphology of ZIF-8, but the surface is relatively rough and accompanied by slight depressions; Figure 1 (b) shows that the ZIF-derived porous carbon material (ZIF-950) has a smooth surface, a regular dodecahedral structure, and uniform particle size; Figure 1 (c) shows that the original morphology of the S-doped porous carbon material (S-ZIF-950) almost completely collapsed into an inhomogeneously aggregated particle state; Figure 1 (d) shows that the Fe-doped magnetic porous carbon material (Fe-ZIF-950) still maintains the original dodecahedral structure, but the skeleton is slightly wrinkled.

[0052] The S / Fe co-doped magnetic porous carbon material prepared in Example 1 was observed by transmission electron microscopy. Figure 1 As shown in (e~f), it can be seen from the figure that S / Fe-ZIF-950 has a typical hexagonal morphology, and a large number of nanoparticles are distributed in the porous carbon matrix. The S / Fe co-doped magnetic porous carbon material prepared by the present invention was observed and analyzed using high-resolution transmission electron microscopy. The results are as follows Figure 1 (g~h), where the lattice spacing of 0.345 nm and 0.214 nm can be pointed to the carbon phase (002) plane and Fe3C (211) plane, respectively, while the lattice spacing of 0.227 nm corresponds to the (102) plane of ZnS, indicating that the composite material prepared by the present invention is composed of Fe3C, ZnS and C. The ring selected area electron diffraction results of S / Fe co-doped magnetic porous carbon material are shown in Figure 1 As shown in (i), the main diffraction ring matches well with S / Fe-ZIF-950. Energy dispersive X-ray spectroscopy (EDS) analysis of the S / Fe co-doped magnetic porous carbon material prepared in the present invention is performed, and the results are as follows Figure 1 As shown in (j), C, N, O, Zn, Fe and S elements are uniformly distributed in the S / Fe co-doped magnetic porous carbon material, proving the successful synthesis of S / Fe-ZIF-950.

[0053] The carbon materials obtained in Example 1 and Comparative Examples 1 to 3 of the present invention were subjected to X-ray diffraction observation and their crystal structures were analyzed. The results are as follows: Figure 2As shown, the four derivative materials all have obvious reflection peaks near 25°, representing the (002) phase of pyrolysis-induced graphitic carbon. No diffraction peaks related to Zn were detected in the porous carbon material ZIF-950, indicating that Zn volatilized at high temperatures. After the introduction of S atoms, the diffraction peaks of S / ZIF-950 were mainly corresponding to zinc sulfide; the graphite peaks in the Fe-doped magnetic porous carbon material Fe-ZIF-950 moved significantly to a higher degree and coincided with the characteristic peaks of Fe3C species; after S and Fe co-doping, the S / Fe-ZIF-950 composite material showed a hybrid structure composed of ZnS, Fe3C and porous carbon. Example 2

[0054] The S / Fe co-doped magnetic porous carbon material prepared in Example 1 of the present invention is used to remove p-chlorophenol in water, specifically comprising the following steps: Take a 1L p-chlorophenol solution with a concentration of 20mg / L, add 0.05g S / Fe co-doped magnetic porous carbon material and 1mM sodium perchlorate, mix well and then carry out periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0055] Control group 1: Take a 1L p-chlorophenol solution with a concentration of 20mg / L, add 0.05g ZIF-8 and 1mM sodium perchlorate, mix well, and then perform periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0056] Control group 2: Take a 1L p-chlorophenol solution with a concentration of 20mg / L, add 0.05g Fe-ZIF-8 and 1mM sodium perchlorate, mix well, and then perform periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0057] Control group three: Take a 1L p-chlorophenol solution with a concentration of 20mg / L, add 0.05g S / Fe-ZIF-8 and 1mM sodium perchlorate, mix well, and then perform periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0058] Control group 4: Take a 1L p-chlorophenol solution with a concentration of 20mg / L, add 0.05g ZIF-950 and 1mM sodium perchlorate, mix well, and then perform periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0059] Control group 5: Take a 1L p-chlorophenol solution with a concentration of 20mg / L, add 0.05g Fe-ZIF-950 and 1mM sodium perchlorate, mix well, and then perform periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0060] Control group 6: Take a 1L p-chlorophenol solution with a concentration of 20mg / L, add 0.05g S-ZIF-950 and 1mM sodium perchlorate, mix well, and then perform periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0061] In addition, without adding sodium periodate, samples were taken from the system to determine the adsorption-desorption of p-chlorophenol by the catalyst, and then periodate was added to initiate the oxidation reaction, which was recorded as time 0 (the time before the addition of periodate was recorded as a negative value). Samples were taken at 1 min, 2 min, 3 min, 4 min, 7 min, 10 min and 13 min after the reaction, and the p-chlorophenol content in the solution was detected by high performance liquid chromatography. The measurement results are shown in the figure. Figure 3 As shown in the figure: when no oxidant is added, each carbon material has a certain adsorption effect on p-chlorophenol, but the S / Fe co-doped magnetic porous carbon material of the present invention has the best catalytic activation effect on the oxidant, wherein p-chlorophenol reaches adsorption-desorption equilibrium on the surface of S / Fe-ZIF-950 in about 10 minutes, and the adsorption rate is 16.1%. After adding sodium periodate, the S / Fe-ZIF-950 / sodium periodate system completely degrades p-chlorophenol within 10 minutes, and the removal efficiency is the highest. The oxidation capacity of ZIF-950, S / ZIF-950 and Fe-ZIF-950 systems is relatively low, and the p-chlorophenol removal rates are 33%, 58% and 42%, respectively. At the same time, under the same reaction conditions, the original ZIF-8 and Fe-ZIF-8 precursors have almost no activation effect on the degradation of p-chlorophenol by sodium periodate, and p-chlorophenol can hardly be removed, indicating that S and Fe co-doping plays an important role in improving the performance of this type of catalyst in activating periodate. Example 3

[0062] This example shows the effect of different amounts of S / Fe co-doped magnetic porous carbon materials on the removal of para-chlorophenol in water. The S / Fe co-doped magnetic porous carbon material prepared in Example 1 is used, and the steps are as follows: Take 5 portions of 1L p-chlorophenol solution with a concentration of 20 mg / L, add 0g, 0.025g, 0.050g, 0.075g, and 0.100g of the S / Fe co-doped magnetic porous carbon material prepared in Example 1, respectively, add 1mM sodium periodate after 10 minutes, and carry out catalytic oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0063] Periodate was added to initiate the oxidation reaction and recorded as time 0. Samples were taken at 1 min, 2 min, 3 min, 4 min, 7 min, 10 min and 13 min after the reaction. The content of p-chlorophenol in the solution was detected by HPLC. The measurement results are shown in Figure 4.

[0064] from Figure 4 It can be seen that as the concentration of S / Fe-ZIF-950 increases from 0.025 g / L to 0.050, 0.075 and 0.100 g / L, the degradation efficiency of p-chlorophenol is significantly improved. At 10 min, the degradation rates of p-chlorophenol in the systems with 0.050, 0.075 and 0.100 g / LS / Fe-ZIF-950 are close to 100%. It can be seen that the increase in the amount of catalyst leads to an increase in the number of active sites for catalytic activation of sodium periodate, which improves the degradation of p-chlorophenol. However, with the continuous increase in the catalyst concentration, the increasing trend of the reaction rate slows down, which is due to the limited concentration of the oxidant. Example 4

[0065] This example is the effect of S / Fe co-doped magnetic porous carbon material on the removal of para-chlorophenol in water under different initial pH conditions. The S / Fe co-doped magnetic porous carbon material prepared in Example 1 is used, and the steps are as follows: Take 4 portions of 1L p-chlorophenol solution with a concentration of 20 mg / L, add 0.050 g of the S / Fe co-doped magnetic porous carbon material prepared in Example 1 to each, and then add 1 mM sodium periodate to each, mix well, adjust the initial pH value of the resulting mixed solution to 3.01, 4.99, 7.00, and 9.00, and carry out sodium periodate activation oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0066] Samples were taken from the reaction system at 1 min, 2 min, 3 min, 4 min, 7 min, 10 min and 13 min of the sodium periodate activation oxidation reaction, and the content of p-chlorophenol in the solution was detected by high performance liquid chromatography. The measurement results are shown in Figure 5 .

[0067] from Figure 5 It can be seen that as the pH increases from 3.01 under acidic conditions to 7.00 under neutral conditions, the removal rate of 4-CP (para-chlorophenol) decreases slightly, but it can still be completely removed within 10 minutes. However, as the pH further increases to 9.00 under alkaline conditions, the removal efficiency of 4-CP (para-chlorophenol) decreases slightly. This shows that the S / Fe co-doped magnetic porous carbon material of the present invention is not highly sensitive to the pH of the solution, and exhibits high activity in a wide pH range, and has a good effect on the removal of wastewater containing para-chlorophenol.

[0068] Depend on Figure 4 , Figure 5It can be seen that the S / Fe co-doped magnetic porous carbon material of the present invention has a good removal effect on p-chlorophenol in water. Under the alkaline conditions of 0.05 g / L S / Fe co-doped magnetic porous carbon material concentration, 1 mM sodium periodate concentration, and 9 initial solution pH, the removal rate of the p-chlorophenol solution with a concentration of 20 mg / L by the method of the present invention can still reach 86%. Therefore, the method of removing p-chlorophenol from water by using S / Fe co-doped magnetic porous carbon material to catalyze sodium periodate can achieve effective degradation of p-chlorophenol wastewater in a wide pH range, and has the advantages of high treatment efficiency, good treatment effect, simple operation, low treatment cost, small amount of catalyst used, and environmental protection. Example 5

[0069] This embodiment shows the effect of different S-doping amounts of magnetic porous carbon materials on the removal of para-chlorophenol in water. The S / Fe-ZIF-950 catalyst material is prepared by the method of Example 1, except that: in step S2, the mass ratios of elemental sulfur to Fe-ZIF-8 are controlled to be 0, 0.05, 0.1, 0.15, and 0.2, respectively, denoted as S / Fe-ZIF-950-X, where X represents the mass ratio of S to Fe-ZIF-8.

[0070] Take 5 portions of 1L p-chlorophenol solution with a concentration of 20 mg / L, add 0.050 g of the prepared S / Fe-ZIF-950-X respectively, add 1 mM sodium periodate after 10 minutes, and carry out catalytic oxidation reaction at room temperature to complete the degradation of p-chlorophenol.

[0071] Periodate was added to initiate the oxidation reaction and recorded as time 0. Samples were taken at 1 min, 2 min, 3 min, 4 min, 7 min, 10 min and 13 min after the reaction. The content of p-chlorophenol in the solution was detected by HPLC. The measurement results are shown in Figure 6 .

[0072] from Figure 6 It can be seen that with the increase of S doping ratio, the degradation rate of 4-CP gradually increases, while the sudden decrease in the performance of S / Fe-ZIF-950-0.2 is due to the structural collapse caused by excessive S doping, which indicates that the S doping amount has an effect on the catalytic activity of S / Fe-ZIF-950. Example 6

[0073] This example is a cyclic stability test of S / Fe co-doped magnetic porous carbon material, using the S / Fe co-doped magnetic porous carbon material prepared in Example 1 to catalyze periodate oxidation and degradation of p-chlorophenol, comprising the following steps: (1) Take 3 portions of 1 L p-chlorophenol solution with a concentration of 20 mg / L, add 0.050 g of the S / Fe co-doped magnetic porous carbon material prepared in Example 1 to the first portion, add 1 mM sodium periodate after 10 min, and carry out catalytic oxidation reaction at room temperature to complete the degradation of p-chlorophenol. After the reaction, separate the S / Fe co-doped magnetic porous carbon material, and then repeatedly wash it with ethanol and water and vacuum dry it for later use.

[0074] (2) The recovered S / Fe co-doped magnetic porous carbon material was used to repeat the catalytic degradation experiment of p-chlorophenol in step (1). A total of three cycles were performed to test the catalytic effect of the material.

[0075] In each cycle experiment, periodate was added to initiate the oxidation reaction and recorded as time 0. Samples were taken at 1 min, 2 min, 3 min, 4 min, 7 min, 10 min, 13 min, 20 min and 30 min of reaction, and the content of p-chlorophenol in the solution was detected by HPLC. The measurement results are shown in Figure 7 .

[0076] from Figure 7 It can be seen that after three experimental cycles, the activity of the catalyst still remains at a high level, and the removal rate of p-chlorophenol exceeds 95%, indicating that the S / Fe co-doped magnetic porous carbon material of the present invention has strong stability, can be recycled, and has a long service life.

[0077] The above is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as above in the preferred embodiment, it is not used to limit the present invention. Any technician familiar with the art can make many possible changes and modifications to the technical solution of the present invention by using the methods and technical contents disclosed above without departing from the spirit and technical solution of the present invention, or modify it into an equivalent embodiment of equivalent changes. Therefore, any simple modification, equivalent replacement, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention, still fall within the scope of protection of the technical solution of the present invention.

Claims

1. A method for preparing a S / Fe co-doped magnetic porous carbon material, characterized in that: A 2-methylimidazole solution is mixed with a zinc salt solution and an organic iron solution for hydrothermal reaction to obtain an iron-containing zeolite imidazolate skeleton precursor; the iron-containing zeolite imidazolate skeleton precursor and elemental sulfur are dispersed in a solvent and heated to obtain a S / Fe co-doped magnetic porous carbon material precursor; the S / Fe co-doped magnetic porous carbon material precursor is subjected to high-temperature pyrolysis under a protective atmosphere to obtain the obtained product.

2. The method for preparing a S / Fe co-doped magnetic porous carbon material according to claim 1, characterized in that: The molar ratio of the 2-methylimidazole to the zinc element in the zinc salt and the iron element in the organic iron solution is (0.5-1.5):(0.1-0.3):(0.01-0.03).

3. The method for preparing a S / Fe co-doped magnetic porous carbon material according to claim 1 or 2, characterized in that: The concentration of the 2-methylimidazole solution is 1-2 mol / L; The concentration of the zinc salt solution is 0.1-0.2 mol / L; The concentration of the organic iron solution is 0.01-0.02 mol / L; The zinc salt is zinc nitrate; The organic iron is iron acetylacetonate.

4. The method for preparing a S / Fe co-doped magnetic porous carbon material according to claim 1, characterized in that: The conditions of the hydrothermal reaction are: temperature of 110-140°C and time of 3-5h.

5. The method for preparing a S / Fe co-doped magnetic porous carbon material according to claim 1, characterized in that: The mass ratio of the iron-containing zeolite imidazolate framework precursor to elemental sulfur is 6-12:

1.

6. The method for preparing a S / Fe co-doped magnetic porous carbon material according to claim 1, characterized in that: The solvent is a mixed solvent of carbon tetrachloride and ethanol; The heating temperature is 50-80°C.

7. The method for preparing a S / Fe co-doped magnetic porous carbon material according to claim 1, characterized in that: The protective atmosphere is an inert gas atmosphere; The high temperature pyrolysis process is: first pyrolyze at a temperature of 400-500° C. for 2-4 hours, and then heat up to 900-1000° C. for 4-6 hours.

8. The method for preparing a S / Fe co-doped magnetic porous carbon material according to claim 1 or 7, characterized in that: The high temperature pyrolysis is followed by an acid leaching and impurity removal treatment.

9. A S / Fe co-doped magnetic porous carbon material, characterized in that: Prepared by the method according to any one of claims 1 to 7.

10. The use of a S / Fe co-doped magnetic porous carbon material according to claim 9, characterized in that: Used to catalyze periodate oxidation and degradation of chlorophenol organic pollutants in solution.

Citation Information

Patent Citations

  • Fe-N codoped porous carbon sphere composite material as well as preparation method and application thereof

    CN108671952A

  • Iron and nitrogen co-doped carbon-oxygen reduction catalyst, and preparation method and application thereof

    CN109103468A

  • Nitrogen-doped graded porous carbon nano catalyst and preparation method thereof

    CN110280286A

  • Preparation method of catalyst for heterogeneous catalytic oxidation of COD in wastewater by hydrogen peroxide

    CN111790445A

  • Preparation method of copper-iron bimetal confinement nitrogen-doped carbon nanotube composite material

    CN113477270A

Cited By

  • Method for constructing double-active-site Fe (FeS) C / PI catalytic oxidation wastewater system

    CN120794151A

  • A method for constructing a dual active site Fe (FeS) C / PI catalytic oxidation wastewater system

    CN120794151B